A VARIATIONIST ANALYSIS OF DEGREE ADVERBS AND ADJECTIVES IN COOKING SHOWS - Hernandez Hernandez, Mariana (WEB REVISTA SOCIODIALETO, 2020)
Este artigo apresenta uma análise de como os chefes de cozinha reproduzem identidades de classe e gênero através da seleção de variantes. O corpus se deriva dos 3,704 adjetivos usados por 12 chefes durante 20 horas de programas de cozinha. Seguindo a classificação de Johnston, Rodney e Chong (2014), os chefes foram classificados em cinco personas culinárias (masculinas: chefe artesão, gastro-sexual, ambientalista; femininas: pin-up e caseira). As duas variáveis estudadas foram 1) advérbios intensificadores (e.g., really great, pretty sticky) e atenuadores (e.g., a bit cold, a little different) modificando adjetivos, e 2) adjetivos modificáveis (e.g., nice, beautiful). Se usou análise multivariada para medir correlações linguísticas (posição sintática e tipo de adjetivo) e sociais (gênero e país), assim como análise qualitativa. A taxa de intensidade (29 %) e os intensificadores mais frequentemente usados (really, very and so) que foram encontrados nos resultados são similares aos encontrados em estudos anteriores sobre advérbios intensificadores (e.g., Ito & Tagliamonte, 2003; Tagliamonte, 2008; Tagliamonte & Roberts, 2005). Os seguintes resultados foram diferentes aos anteriores: (1) a construção nice and (que inclui lovely and e good and) apareceu no quarto lugar, no qual geralmente aparece outra variante (e.g., pretty ou absolutely); (2) os advérbios atenuadores apareceram bem distribuídos, e parecem estar marcando controle culinário; (3) os advérbios intensificadores que terminam em -ly pareceram indicar masculinidade. ABSTRACT: This paper presents an analysis of how food celebrities reproduce gender and class identities through variant choice. The corpus (3,704 adjectival heads) is derived from 20 hours of televised cooking shows from twelve food celebrities from Canada, England, and the USA. They were classified in five gendered culinary personas (male: chef-artisan, gastro-sexual, environmentalist; female: pin-ups and homebodies), based on Johnston, Rodney and Chong’s categorization (2014). The two linguistic variables that are the focus of this paper are 1) degree adverbs preceding adjectives: intensifiers (e.g., really great, pretty sticky) and attenuators (e.g., a bit cold, a little different), and 2) gradable adjectives (e.g., nice, beautiful). Multivariate analysis was used to measure linguistic (syntactic position and adjective type) and social (gender, country) correlations, as well as qualitative analysis. The intensification rates (29 %) and the three most frequently used intensifiers (really, very and so) found in the results were similar to those found in previous intensifier studies (e.g., Ito & Tagliamonte, 2003; Tagliamonte, 2008; Tagliamonte & Roberts, 2005). The following results were different from previous findings: (1) the nice and construction (which included lovely and and good and) appeared in the fourth place, which is usually taken by another variant (e.g., pretty or absolutely); (2) attenuators were well distributed, and they seemed to mark culinary control; and (3) −ly intensifiers seemed to indicate masculinity. KEYWORDS: Adjectives; Degree adverbs; Linguistic variation; Cooking shows.